Virus free seed potato production through sprout cutting technique under net-house - Karim, M. R.; Musa, Mohamed Hanafi; Shahidullah, S. M.; Rahman, A. H. M. A.; Akanda, A. M.; Khair, A. (Academic Journals, 2010)
In order to evaluate the performance of sprout cutting for seed potato production against virus infection, a study was conducted at Bangladesh Agricultural Development Corporation (BADC) Foundation Seed Potato Production Farm, Domar, Nilphamary, Bangladesh in 2005 - 2006. Sprout cut seedlings were grown under three production practices viz. Net-house practice, BADC practice and farmers’ practice. Sprout cutting technique was proved to be an effective method of seed potato production against potato virus Y (PVY) and potato leaf roll virus (PLRV). The incidence of PVY and PLRV was detected as nil in net-house practice. However, PVY and PLRV were prevalent in BADC practice and farmers’ practice although, BADC practice performed better over farmers’ practice. Yield of seed potato and non-seed tubers along with yield attributes were found to be higher in all the five varieties (Diamant, Baraka, Asterix, Raja and Provento) in net-house practice followed by BADC practice and farmers’ practice. Among the varieties Diamant, Asterix and Raja seemed to be better in performance as compared to the others. In most of the cases net-house practice differed significantly (p = 0.05) with the others.